The Relationship of Transformational Leadership Style and Transactional Leadership Style on Employee Performance - Putra, Briyan Cadalora; Sa'adah, Ummi; Nitawati, Elly Yuniar; Iman, Nurul; Jannah, Raudatul (PT FORMOSA CENDEKIA GLOBAL, 2024)
Companies must keep improving themselves by increasing their resources to cope with severe competition. In order for a company to survive, it must be able to deal with problems from within and from outside. The study aims to investigate how transformational and transactional leadership styles affect employee performance. The study involved 50 employees of the Ni Made Tjandra Kasih Public Assessment Office in Surabaya. Fifty employees of Ni Made tjandra kasih public assessment office in Surabaya consisted of different levels of management, occupational responsibilities, gender, and educational backgrounds. The research found that transformational leadership and transactional leadership improved employee performance at the Ni Made Tjandra Kasih Surabaya Public Assessment Office, and that transformative leadership as well as transactional leadership also improved employees performance.